Major Extremity Injuries Associated with Farmyard Accidents - Cem Copuroglu; Nurettin Heybeli; Mert Ozcan; Baris Yilmaz; Mert Ciftdemir; Elif Copuroglu (The Scientific World Journal)
Background. The aim of the study is to analyze the major agricultural injuries related to the extremities. Patients. We evaluated a 3-year period including 41 patients. Data on age, sex, injury patterns, anatomical localizations, injury season, length of stay in the hospital, and infections were evaluated, and the patients were examined with SF-36 in the follow-up period. Results. Hand was the most commonly injured part (n: 9) followed by the distal part of the lower limb (cruris) (n: 7) and foot (n: 7). Mean time between trauma and emergency-department arrival was 115 minutes (60–360). Mean length of stay was 24 days (4–150), and mean number of operations during hospitalization was 2.4 (1–30). Deep wound infection was seen in 8 patients. Seasonal distribution for accidents was even for spring and fall (27% each), high for summer (36%), and less for winter (10%). Conclusions. Distal parts of the elbow and knee were affected more frequently. Due to the high microbiological load and high incidence of crush-type injuries, repetitive debridements and long duration of hospital stay were needed. Attention should be paid in the harvesting times to the farmyard injuries. Due to the seasonal variation, more resources should be allocated to treat the increasing incidence of injury over the period from spring to fall.